Smart Phone Addiction: diagnosis and management - Dr. Magesh Rajagopal (Tamil Psychiatry Journal, 2025)
The 21st century has become the century of information technology. Since the introduction of smartphones in 2007, they have gradually become an indispensable device in our lives. In the last ten years, smartphone use has grown exponentially worldwide and by 2020, nearly 2.8 billion people are using them. Smartphones, which can provide great benefits to humanity, also provide many unnecessary things that can spoil the human mind. For example, it has created a situation where things like online gambling, internet gaming and pornography can be viewed regardless of age. For many reasons, using smartphones continuously for hours together creates a state of dependence on that smartphone. A study conducted by Nikita in Mumbai found that 31% of people are addicted to mobile phones. Similarly, studies conducted in England and Italy have found that mobile phone addiction is most prevalent among adolescents aged 11 to 15. This article discusses in detail the symptoms of mobile phone addiction and various harmful effects of mobile phone addiction. It also includes a brief note on internet game addiction, cyber ​​relationship addiction, internet information addiction and internet shopping addiction. Prevention and management strategies for mobile phone addiction is also discussed here.